2015
DOI: 10.1136/bmjopen-2015-008610
|View full text |Cite
|
Sign up to set email alerts
|

Development of a universal approach to increase physical activity among adolescents: the GoActive intervention

Abstract: Objectives: To develop a physical activity (PA) promotion intervention for adolescents using a process addressing gaps in the literature while considering participant engagement. We describe the initial development stages; (1) existing evidence, (2) large scale opinion gathering and (3) developmental qualitative work, aiming (A) to gain insight into how to increase PA among the whole of year 9 (13-14 years-old) by identifying elements for intervention inclusion (B) to improve participant engagement and (C) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 61 publications
3
72
1
Order By: Relevance
“…The researchers found that adolescents prefer strategies that promote healthy eating, such as showing healthy alternatives, to those that discourage unhealthy eating. Also, in terms of physical activities, studies have highlighted that it is important to provide opportunities for adolescents to try new activities as it could overcome barriers to engaging in sport activities (Corder, Schiff, Kesten, & Van Sluijs, 2015). By trying these activities in the intervention, the adolescents mentioned that it made them try other activities outside the intervention, such as going to the gym or preparing more healthy meals at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that adolescents prefer strategies that promote healthy eating, such as showing healthy alternatives, to those that discourage unhealthy eating. Also, in terms of physical activities, studies have highlighted that it is important to provide opportunities for adolescents to try new activities as it could overcome barriers to engaging in sport activities (Corder, Schiff, Kesten, & Van Sluijs, 2015). By trying these activities in the intervention, the adolescents mentioned that it made them try other activities outside the intervention, such as going to the gym or preparing more healthy meals at home.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of trying new activities, the adolescents also emphasized that sport instruction was valuable, which might be necessary if the activity is new. Other studies have cited the interest of adolescents in using mentors to instruct them in physical activities (Corder et al, 2015). Finally, it is important to consider the group dynamic.…”
Section: Discussionmentioning
confidence: 99%
“…The GoActive intention has been described in detail previously,13 and the components are presented in table 1. Briefly, GoActive aims to increase PA through increased peer support, self-efficacy, self-esteem, group cohesion and friendship quality, and is implemented in tutor groups using a tiered leadership system (figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously described the development process of the GoActive intervention aiming to increase PA among 13–14 years old adolescents 13. This process included identifying gaps in the existing literature, large-scale quantitative adolescent opinion gathering,1 adolescent and teacher focus groups, adolescent interviews investigating engagement of the target group and development and refinement of the intervention 13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation